Analisis Sistem Informasi Akuntansi Pengeluaran Kas Uang Ganti Kerugian Pengadaan Tanah Jalan Tol Simpang Indralaya Muara Enim Di Kementrian PUPR - Hilwa Anggraini; Masnoni; Zein Ghozali; Irsan; Sri Sutandi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to determine the accounting information system for cash disbursements for compensation for land acquisition for the Simpang Indralaya- Muara Enim toll road. The type of research is case study with data collection methods carried out by literature studies and field studies and data collection techniques through observation, interviews, and documentation. The data used is descriptive qualitative data. The source of the data obtained is primary data from the office of the Land Procurement Commitment Officer for the Simpang Indralaya-Muara Enim Toll Road and secondary data obtained from journals, theses, andapplicable regulations. The problem is that the accounting information system for cash disbursements for compensation for land acquisition on the Indralaya-Muara Enim Intersection is still weak. This is due to the lessthan optimal function of the examiner of the Commitment Making Officer so that there are documents for the provision of compensation money which are declared incomplete according to the Supreme Audit Agency. Based on the results of the qualitative descriptive analysis, the Land Procurement Implementing Agency and the Land Procurement Commitment Officer for the Indralaya-Muara Enim Intersection should form an internal verifier team. It is hoped that by forming an internal verifier team, it can minimize document incompleteness so that document completeness can be optimized.